Penghindaran Pajak: Apakah Perusahaan Yang Bertanggung Jawab Secara Sosial Patuh Terhadap Pajak? - Truly Wulandari; Arum Prastiwi; Sari Atmini (Universitas Muhammadiyah Malang, 2022)
This study aims to examine and analyze the relationship of corporate social responsibility disclosure to tax avoidance with profitability as a moderating variable. The population in this study are all companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sample selection in this research using the purposive sampling method and obtained 515 observations from 103 sample companies with a five-year observation period. The analytical method used in this study is Moderated Regression Analysis (MRA). The results also show that companies with good quality CSR disclosure tend to have low levels of tax avoidance. The results of this study found evidence that companies with good CSR disclosure quality are more tax compliant when they have high profitability. This research is additional empirical evidence to support legitimacy theory as the basis for the relationship between CSR disclosure and tax avoidance. The results illustrate that CSR disclosure must be considered by investors before investing in a company. The quality of CSR disclosure reflects a company's commitment to conducting business in an ethical manner and reduces the possibility of a company to engage in tax avoidance.